EDITORIAL - Martin Oliver; Grainne Conole; Jane Seale (Association for Learning Technology, 2004)
This issue marks a new beginning for ALT-J; it is the first with our new publishers, Taylor & Francis, under their Carfax imprint. Re-launching a journal is, we have found, an interesting process. Like moving house or changing jobs, it manages to blend logistical complications with a rare opportunity to pause, reflect and take stock. It isn't often that we have the chance to re-assess what is important to us, so as editors we grasped this particular challenge with glee.